INTEGRATED LANGUAGE LEARNING IN ESTONIAN NATIONAL CURRICULA (NC) FOR GENERAL COMPREHENSIVE SCHOOLS - Läänemets, Urve; Kalamees-Ruubel, Katrin (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Multiple language skills have become a critical issue in the globalised world. The EU education strategy 2020 document includes mother tongue and two foreign languages among its key competencies to be achieved. To promote learning with comprehension, an integrated approach to curriculum design can be taken, including a cycle of language subjects that makes use of both the manifest and hidden curricula as well as different learning environments. The 21st century approach to education requires from all school staff not only technical but considerable intellectual competence. Language learning is expected to meet the regional and local demand for particular language skills, which is determined by regular monitoring according to functional styles.